Rancang Bangun Alat Pengering Bahan Makanan Teknologi Cerdas Berbasis Arduino untuk Produktivitas UMKM - Oaleya Fahad Ibrahim; Mohammad Riza Radyanto (Industrika : Jurnal Ilmiah Teknik Industri, 2026)
Micro, Small, and Medium Enterprises (MSMEs) in Indonesia still largely rely on traditional drying methods, such as sun drying, which are inefficient during rainy seasons. This study aims to design and test a food drying system based on Arduino Uno and Internet of Things (IoT) to enhance drying efficiency and production quality. The system integrates a DHT11 sensor for automatic temperature and humidity monitoring, combined with a blower, heating element, and digital timer. Research was conducted using experimental and development methods at the Industrial Engineering Laboratory of STIKUBANK University, Semarang. Results show a significant reduction in moisture content, with the highest reduction found in crackers (92.5%). Regression and ANOVA analysis confirmed that temperature and drying time significantly affect drying efficiency, while humidity has less impact. The system improved hygiene, consistency, and reduced weather dependency, making it a suitable solution for MSME productivity. Keywords: Arduino, Drying, Efficiency, IoT, Sensor